The Role of Brand Trust in Mediating Effect of Brand Image on Purchasing Decision at Unilever Products - Silvia Tria Lestari; Saputra, Febrian Eko (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze how Brand Trust acts as a link between Brand Image and purchasing decisions for Unilever products in Bandar Lampung City. The method used is quantitative, with data collected through questionnaires. This study involved consumers of Unilever products in Bandar Lampung City as a population. Because exact data on population size was not available, respondents were selected using non-probability sampling method and purposive sampling technique, focusing on Gen Z consumers who have purchased Unilever products in Bandar Lampung. Data were analyzed using Structural Equation Modeling (SEM) and Partial Least Square (PLS). The results of this study reveal that Brand Image has a significant effect on purchasing decisions through Brand Trust on Unilever products. Brand Image has a positive effect on Purchasing Decisions, Brand Trust affects Purchasing Decisions. Brand Trust mediates the influence of Brand Image on purchasing decisions.